Driving under the Influence of Amphetamine: Analytical Evaluation of Illegal or Prescription Drug Intake Using Chiral UHPLC–MS-MS. Issue 3 (16th December 2022) - Nielsen, Marie Katrine Klose; Andersen, Nina Zacho; Rasmussen, Brian Schou; Johansen, Sys Stybe
Abstract: Differentiation between consumption of illegal and prescription drugs remains an important aspect in forensic toxicology. While illicit amphetamine is most often racemic, the medicinal drugs marketed in Denmark for the treatment of attention-deficit hyperactivity disorder contain the pure ( S )-enantiomer or a prodrug thereof. In this study, we present a simple and efficient analytical workflow to provide information about the origin of amphetamine consumed in forensic cases concerning driving under the influence of drugs (DUID). Following quantification of amphetamine and methamphetamine using our conventional multi-target ultra-high performance liquid chromatography–tandem mass spectrometry method, determination of ( R )- and ( S )-amphetamine was performed by reinjecting the sample extract on a Phenomenex LUX ® AMP chiral column using the same analytical instrument and mobile phases. Chiral separation was performed isocratic within a run time of 6 min. The analytical workflow was applied to blood samples from 5, 248 suspected DUID cases within a 2-year period. Amphetamine was detected in 18.7% of the samples, of which both enantiomers were detected in 89.5% of the cases, indicating the consumption of illegal racemic amphetamine. In 6.1% of the positive cases, both amphetamine and methamphetamine were detected, indicating either co-consumption of both amphetamines or consumption of methamphetamine. In the remaining 4.4%, only ( S )-amphetamine was detected indicating the consumption of prescription drugs containing ( S )-amphetamine or a prodrug thereof. Implementation of a simple and rapid chiral method in the conventional analytical workflow for routine forensic casework proved to be an efficient way to elucidate whether a positive amphetamine result originates from illegal or prescription drug consumption, without increasing turnaround time nor costs to any significant extent, as no additional sample preparation was required.